Diffraction studies under in situ electric field using a large‐area hybrid pixel XPAD detector. (21st July 2013) - Fertey, Pierre; Alle, Paul; Wenger, Emmanuel; Dinkespiler, Bernard; Cambon, Olivier; Haines, Julien; Hustache, Stephanie; Medjoubi, Kadda; Picca, Frederic; Dawiec, Arkadiusz; Breugnon, Patrick; Delpierre, Pierre; et al.
<x xml:space="preserve">Abstract</x> A new experimental approach to perform in situ electric field diffraction on single crystals using an on‐then‐off pump–probe mode in situ (i.e. the field‐switching method) with a synchrotron or a laboratory X‐ray source is presented. Taking advantage of the fast readout of the XPAD hybrid pixel two‐dimensional detector and its programmable functionalities, the operation mode of the detector has been customized to significantly increase the efficiency of the method. The very weak electric field‐induced structural response of a piezoelectric crystal can be accurately measured. This allows the piezoelectric tensor to be precisely obtained from Δθ shifts while the structural variations can be modelled using a full set of ΔI/I data. The experimental method and methodology are detailed and tested as a case study on pure piezoelectric compounds belonging to the α‐quartz family (SiO2 and GaAsO4 single crystals). Using the two scan modes developed, it is demonstrated that tiny Bragg angle shifts can be measured as well as small field‐induced Bragg intensity variations (<1%). The relevance of measurements performed with an X‐ray laboratory source is demonstrated: partial data sets collected at synchrotrons can be completed, but more interestingly, a large part of the study can now be realized in the laboratory (medium to strong intensity reflections) in a comparable data collection time.